Trimester-specific phthalate concentrations and glucose levels among women from a fertility clinic - Tamarra M. James-Todd; Yu-Han Chiu; Carmen Messerlian; Lidia Mínguez-Alarcón; Jennifer B. Ford; Myra Keller; John Petrozza; Paige L. Williams; Xiaoyun Ye; Antonia M. Calafat; Russ Hauser; EARTH Study Team (BMC, 2018)
Abstract Background Subfertile women are at increased risk of glucose intolerance in pregnancy. Based on epidemiologic studies, exposure to certain phthalates is associated with diabetes, elevated glucose, and increased insulin resistance. Objectives To evaluate the association between urinary phthalate metabolites and pregnancy glucose levels in women seeking medically assisted reproduction. Methods We evaluated 245 women participating in a prospective cohort study based at a large fertility clinic who delivered live births and had data on pregnancy urinary phthalate metabolite concentrations and blood glucose levels. Urinary phthalate metabolite concentrations were from single spot urine samples collected in 1st and 2nd trimesters. Blood glucose data was abstracted from medical records for non-fasting 50-g glucose challenge tests at 24-28 weeks gestation. Multivariable linear regression models were used to evaluate associations between 7 urinary phthalate metabolites in quartiles and mean glucose adjusted for potential confounders. Results Eighteen percent of women had glucose levels ≥ 140 mg/dL. Second trimester monoethyl phthalate (MEP) concentrations were positively associated with glucose levels, with adjusted mean (95%CI) glucose levels of 121 mg/dl (114, 128) vs. 109 mg/dL (103, 116) for women in highest and lowest quartiles, respectively. Women in the highest quartile of second trimester mono-isobutyl phthalate (MiBP) concentrations had a mean glucose level 14 mg/dL lower compared to women in the lowest quartile. No other urinary phthalate metabolites were associated with glucose levels. Conclusions MEP and MiBP-metabolites of diethyl phthalate and dibutyl phthalate, respectively-were associated with higher pregnancy glucose in subfertile women-a population at high risk of glucose intolerance in pregnancy.